Социокультурный подход в социогуманитарных науках: обмен смыслами - Черныш, Н.; Ровенчак, О. (Социология: теория, методы, маркетинг, 2005)
The main goal of the article is to analyze the stage of main socio-cultural approach
provisions working out in socio-humanities and senses exchange between philosophy
and sociology in terms of given approach. The analysis concerns famous Ukrainian
and Russian scientists’ works that contain provisions of socio-cultural approach
essence and its applying in contemporary post-communist societies (first of all
Ukrainian and Russian ones) studying.